Consumption lives at the bottom of the pyramid. (September 2013) - Piacentini, Maria; Hamilton, Kathy
Over the last decade, there has been increasing recognition of the value of understanding the lives of people throughout the world who experience impoverishment. 'Bottom of the pyramid' is the term used to describe people living in absolute poverty who, despite economic limitations, can be 'resilient entrepreneurs' and co-creators of new market opportunities that result in win-win situations for companies and consumers (Prahalad, 2004: 3). A range of metrics are used to define and describe people living in poverty, and although these metrics help identify the neediest across the world, such measures exclude people living in developed nations where poverty exists on a large scale, but where welfare policy provides a safety net. In this essay, we discuss some of the issues for those living in poverty in both developed and developing countries and argue that this will lead to a deeper understanding of the consumption experiences of those living in poverty.